B-type natriuretic peptide for prediction of incident clinically significant abdominal aortic aneurysm: A population-based prospective study. (February 2018) - Acosta, Stefan; Gottsäter, Anders; Engström, Gunnar; Melander, Olle; Zarrouk, Moncef; Nilsson, Peter M; Smith, J Gustav
Pathogenesis of abdominal aortic aneurysm (AAA) is unclear. The aim of this study was to evaluate inflammatory and hemodynamic plasma biomarkers as predictors for AAA in the prospective longitudinal cohort of middle-aged individuals from the cardiovascular cohort of the Malmö Diet and Cancer Study ( n =5551; 1991–94). C-reactive protein, cystatin C, copeptin, N-terminal pro-B-type natriuretic peptide (N-BNP), midregional pro-atrial natriuretic peptide (MR-proANP) and conventional risk factors at baseline were measured in patients with incident AAA during follow-up and compared to individuals without a diagnosis of AAA. Subjects were followed until 31 December 2013. Multivariable analyses were expressed in terms of hazard ratios (HR) per 1 standard deviation increment of each respective log-transformed plasma biomarker in the Cox proportional hazard models. Mean follow-up time was 20.7 years. Cumulative incidence of AAA was 1.5% (men 2.9%, women 0.5%). Mean age of individuals with incident AAA was 59.7 years at study entry and AAA was diagnosed on average 14 years later. Adjusting for age, sex, smoking, body mass index, hypertension and diabetes mellitus, N-BNP (HR 1.29; 95% CI 1.03–1.62), but not MR-proANP (HR 1.20; 95% CI 0.95–1.50), was independently associated with incident AAA. In conclusion, the plasma biomarker N-BNP was associated with future development of AAA, which implies that this marker is a sensitive indicator of early subclinical cardiovascular disease.